2022
DOI: 10.3390/ijerph191711038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family Functioning on Adolescent Materialism and Egocentrism in Mainland China: Positive Youth Development Attributes as a Mediator

Abstract: Although adolescent materialism and egocentrism are growing problems in Chinese societies, there are very few studies investigating their predictors and related mediators. Longitudinal studies in this area are also sparse. Based on a short-term longitudinal study (n = 4981), we assessed the impact of family functioning on materialism and egocentrism of Chinese adolescents, with positive youth development attributes as a hypothesized mediating factor. Results showed that family functioning positively predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…To equate higher item scores with better family functioning, all responses of positive items were reverse-coded. C-FAI has been found to be valid and reliable in previous research utilizing Chinese adolescents (e.g., Shek et al, 2022a , b , 2023 ). In this study, both first-order and second-order factor structures of family functioning were empirically supported.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…To equate higher item scores with better family functioning, all responses of positive items were reverse-coded. C-FAI has been found to be valid and reliable in previous research utilizing Chinese adolescents (e.g., Shek et al, 2022a , b , 2023 ). In this study, both first-order and second-order factor structures of family functioning were empirically supported.…”
Section: Methodsmentioning
confidence: 80%
“…In this study, both first-order and second-order factor structures of family functioning were empirically supported. The CFA results of this study were the same as those in Shek et al’s (2022a , b) study as the dataset used was the same for this study and Shek et al’s ones. In sum, five primary factors and a higher-order factor of the C-FAI have been identified.…”
Section: Methodsmentioning
confidence: 89%
“…Gender, age, and ethnicity were all considered covariates in this study and were controlled in all models and analyses. Previous studies have indicated that these variables are likely to be correlated with family functioning and adolescent development ( Shek et al, 2022b , c ). As Sichuan Province’s diverse population includes a number of minority groups, considering ethnicity helps in examining potential differences in experiences and perceptions between students from different ethnic groups.…”
Section: Methodsmentioning
confidence: 99%
“…Research Question 1: Does family functioning predict resilience in children concurrently and longitudinally? Based on the “Family Resilience Theoretical Framework” ( Walsh, 1996 ) as well as previous studies ( Rosenblum et al, 2005 ; Sahanowas and Halder, 2019 ; Shek et al, 2022b , c ), we proposed two hypotheses:…”
Section: Introductionmentioning
confidence: 99%
“…Future research should explore the interaction of other individual factors (eg, psychological capital and physical exercise) and environmental factors (eg, family and school) on the positive development patterns of left-behind adolescents for a more comprehensive understanding. [78][79][80][81] Secondly, sample collection may have been subject to selection bias, limiting the generalizability of our findings to other populations (eg, other grades and regions) of left-behind adolescents. Moreover, the scales used in this study were developed for Chinese populations, necessitating further validation for cross-cultural applicability.…”
Section: Contributions and Limitationsmentioning
confidence: 99%